The Effect of Internal Displacement on Social Structure in Iraq - Omar, Yazid Salim (Raudhah Publisher, 2024)
Internal displacement in Iraq, triggered by armed conflict, sectarian violence, and political instability, has had a significant impact on the social fabric of the country. This phenomenon creates fundamental changes in community dynamics, social interactions, and family networks. This study aims to analyze how internal displacement affects social structures in Iraq, with a focus on changing patterns of social interaction, community cohesion, and gender roles. This study uses a qualitative method with a case study approach to collect data from various internally displaced groups in the main regions of Iraq. Data were obtained through in-depth interviews, participatory observations, and document analysis to gain a comprehensive understanding of the social impacts of internal displacement. The results show that internal displacement has led to community disintegration, gender role changes, and increased social inequality. In addition, displacement also exacerbates the problems of poverty and access to basic services, which in turn strengthens social tensions and weakens community cohesion. The study concludes that internal displacement in Iraq has an impact not only on the material dimension but also on deeper social aspects, which require special attention in post-conflict reconstruction and social integration policies.